D’une pratique incarnée de l’espace architecturé à une dynamique de l’intériorité : autour de l’ingénierie domestique et d’une féminisation de l’emprise sur l’espace domestique - LaSalle, Virginie (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2023)
This article highlights the modalities of research-creation practices in the context of the historical movement known as domestic engineering (late-nineteenth/early-twentieth century), particularly through the publications of Catharine Esther Beecher and Christine Frederick. The paper further argues that the research-creation specific to this movement is the precursor of a human-centered design position and participates in the foundations of contemporary practices in interior design and architecture, which aspire to anchor their productions in use and scientific rigor. As a starting point, this article discusses the conditions of emergence of the movement. Four key moments of the converging practices of research-creation and domestic engineering are identified: critical positioning, the scientific method, innovative design proposals, and the dissemination of those proposals.